The effect of moderate alcohol drinking in nonalcoholic fatty liver disease - Jong Hwa Choi (Clinical and Molecular Hepatology, 2020)
Nonalcoholic fatty liver disease (NAFLD) is defined by fat accumulation in liver that is not caused by excessive alcohol consumption. Safe limits of alcohol consumption in NAFLD are usually defined as alcohol consumption of less than 210 g per week for men and 140 g per week for women (30 g/day in men, 20 g/day in women) and alcohol consumption below safe limits is generally regarded as moderate alcohol consumption. Many studies have investigated the effects of moderate alcohol consumption on NAFLD patients. Some studies showed that moderate alcohol consumption prevented the progression of fibrosis in the liver, whereas other reports showed worsening of fibrosis in the liver based on serologic, radiologic and liver biopsy findings compared with effects on total abstainers. NAFLD is also thought to be a hepatic manifestation of metabolic syndrome, and when combined with excessive alcohol consumption results in the development of components of metabolic syndrome and systemic harmful effects. The effects of moderate alcohol consumption on NAFLD have yet to be established.